Ion Association Constants and Calculation of Thermodynamic Parameters of N-[(benzoyl-amino) thioxomethyl] Serine Copper (II) Chloride in Methanol + Water Mixed Solvents - Lalrosanga , .; Singh, N. Mohondas (Challenges and Advances in Chemical Science Vol. 7, 2021)
Conductance values of a complex, N-[(benzoyl-amino) thioxomethyl] serine copper (II) chloride was estimated in methanol-water mixed solvents, viz., Xmethanol=0.0000-1.0000 at temperature ranges 283.15 to 313.15 K. From the experimental results, the ion association constants (KA ) and limiting equivalent conductance (\(Λ\)0 ) were determined by analyzing conductivity data concerning Shedlovsky equations for the electrolytes. The Walden product, (\(Λ\)0 \(η\)0 ) values were calculated in various water + methanol mixtures at 283.15 to 313.15 K. It was observed that the increase in the percentage of methanol results in an increase in association constant values. It was also found that with the increase in KA values dielectric constant values were also increased. Increase in KA values with the increase in the dielectric constants of the mixtures. \(Λ\)0values linearly increased as the increased in temperature. Thermodynamic factors were calculated from the KA s and the results we got were examined.